The Equipment of a Laboratory for Metallurgical Chemistry in a Technical School - C. H. White (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
Discussion of a Paper by Mr. C. H. White, read at the Atlantic City Meeting, February, 1904. (Annual Meeting, February, 1005.) ARTHUR JARMAN, Sydney, New South Wales, Australia (communication to the Secretary*) : All designs for modern metal¬lurgical and chemical laboratories should provide each student's desk with a hood or cupboard for the removal of fumes, but I doubt the advisability of placing air-baths and similar apparatus close to the hot plate. It seems to me that unless the draft be exceptionally strong the fumes from ordinary wet assay work will corrode the iron-work of the fittings, in which case the baths would have to be removed to a general desk in order to lighten the work of the laboratory attendant. Since the laboratory described by Mr. White has been in use for two years, I should like to ask if any inconvenience has resulted from this corrosion. If not, it is certainly an important improvement to have the air-baths and similar apparatus placed -on the student's desk. The hoods described by Mr. White are supplied with a good draft by means of a fan, which gives them a great advantage over those at the metallurgical laboratory at the University, Sydney, in that no doors to the hood are needed. Each hood in the laboratory at Sydney is connected by a glazed earthenware drain-pipe with a vertical flue, 20 ft. high, having a lighted gas jet at the bottom to assist the draft. Although the draft is good, fumes of sulphuric acid cannot be drawn o$ unless the doors of the hood are lowered more than half-way. In my opinion, a fan should be used for the purpose of creating the draft, and glazed drain-tile should invariably be used for the flues because no other material possesses the same advantages. I know of a recent instance in which a laboratory containing